Investor Tax Breaks and Financing for Start-Ups: Evidence from China - İrem Güçeri; Xipei Hou; Jing Xing (CESifo GmbH, 2024)
We examine how investor-level tax incentives affect financing for start-ups using the introduction of a generous tax deduction for qualified angel and VC investment in China as a quasi-natural experiment. We find that the tax incentive increases funding for eligible start-ups, with stronger responses from larger and more experienced investors. The tax incentive leads to substitution between eligible and non-eligible investments. There is no evidence that the tax incentive lowers investment quality. We further show that the investor-level tax incentive encourages firm entry into affected industries, especially in cities more exposed to venture capital funds.
Keywords: G24; G32; H25; L26; 330; venture capital; angel investment; tax incentives; entrepreneurship